Liability of Goods Delivery Service Providers for Employee Misconduct Causing Harm to Consumers - Chezia Maharany; Surahmad Surahmad (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2026)
The rapid expansion of e-commerce has increased reliance on goods delivery services while simultaneously generating more disputes concerning consumer losses arising from employees' conduct during service performance. Although Indonesian consumer protection law recognizes the liability of business actors, the scope of that liability remains contested when losses result directly from employees' actions rather than institutional policies. This study examines the legal relationship among business actors, employees, and consumers, and evaluates the normative basis of business actors' liability through an analysis of Supreme Court Decision Number 175 K/Pdt.Sus-BPSK/2021. Employing normative juridical research with statutory and case approaches, the study analyzes legislation, judicial decisions, and legal doctrine to clarify the allocation of legal responsibility within consumer transactions. The findings demonstrate that business actors bear primary responsibility for consumer losses caused by employees acting within the scope of their employment, regardless of whether the misconduct reflects individual negligence or institutional fault. This conclusion is grounded in the principles of consumer protection and vicarious liability under Indonesian law. The study contributes to consumer protection scholarship by developing a coherent framework for attributing liability to business actors, thereby strengthening legal certainty, enhancing consumer remedies, and providing clearer guidance for dispute resolution.